A Generic Drug Policy as Cornerstone to Essential Medicines in China - World Bank (Washington, DC, 2017)
Compared with developed economies, health expenditure in China is not particularly high on a per capita basis or as a share of Gross Domestic Product (GDP). Similarly, pharmaceutical expenditure in comparative perspective is not particularly high on a per capita basis or as a percentage of GDP. China's exceptionally high rate of pharmaceutical expenditure has important implications for the future of a health care system that not only serves a rapidly aging population, but encourages overuse of drugs in ways that are both financially and medically inefficient. Pharmaceutical reform is therefore a high priority for China's health policymakers. Several factors are discussed for reforming this system based on lessons from recent reforms. The section following this introduction briefly reviews the expansion of basic medical insurance coverage in the 2000s and several structural features of the pharmaceutical sector in China. The related concepts of an essential medicines policy, an essential drug list, and a generic drug policy are briefly described in first section. The second section of the paper looks at several hurdles that are built into the path of essential medicines reform. The third section considers some lessons for pharmaceutical reform based on China's recent learning from regional experimentation and piloting initiatives. The fourth section considers several relevant lessons derived from reform experiences in other countries. The fifth section looks at the path forward-success factors for implementing an essential medicines program based on low-cost generic drugs.